2023
DOI: 10.3390/ma16165604
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Superelastic Nickel–Titanium Wires after Clinical Use

Inés Alcaraz,
Javier Moyano,
Ariadna Pàmies
et al.

Abstract: The aim of the present study was to describe and determine changes in the superelastic properties of NiTi archwires after clinical use and sterilization. Ten archwires from five different manufacturers (GAC, 3M, ODS, GC, FOR) were cut into two segments and evaluated using a three-point bending test in accordance with ISO 14841:2006. The center of each segment was deflected to 3.1 mm and then unloaded to 0 N to obtain a load–deflection curve. Deflection at the end of the plateau and forces at 3, 2, 1 and 0.5 mm… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 36 publications
(65 reference statements)
0
1
0
Order By: Relevance
“…In 2023, Alcaraz et al [ 76 ] studied five different NiTi archwires from five different manufacturers (GAC, 3M, ODS, GC, and FOR) using a three-point bending test with the aim of describing and statistically determining the changes to their superelastic properties following clinical use and sterilization. The study found that, following three months of clinical use, FOR exhibited a longer activation period and a larger release of force.…”
Section: Overview Of Various Studies On the Bio-active™ And Contempor...mentioning
confidence: 99%
“…In 2023, Alcaraz et al [ 76 ] studied five different NiTi archwires from five different manufacturers (GAC, 3M, ODS, GC, and FOR) using a three-point bending test with the aim of describing and statistically determining the changes to their superelastic properties following clinical use and sterilization. The study found that, following three months of clinical use, FOR exhibited a longer activation period and a larger release of force.…”
Section: Overview Of Various Studies On the Bio-active™ And Contempor...mentioning
confidence: 99%